Agribisnis Tanaman Obat Kunyit dan Lengkuas - Priyono - - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACTTurmuric plant and galangal is plant that have been populist, Indonesiannation has been known since forebear trade in Nusantara, also known even inChina, Babillonia, and Egypt, because has many benefits, such as for staple foodseasoning to a variety of cakes and sweets, trditional medicine is natural and freeof artificial chemical in the form of herbal medicine, skin medications, cosmeticand etc. but all serves to keep and increase human health, or increase livelihoodand both society and the state economy.Remember the benefits very higher, then it’s development needs to be putonly traditional but also modern such us processing and packaging are eitherfixed without chemical preservatives and marketing in a professional and nothave to change their traditional characteristic coming from the common people.For turmeric and galangal succesfull, it needs to be prepared early andwell planned, that’s from attitude preparation, adequate capital, seed and goodsoil, maintanane involves fertilizing, watering, pest and desease eradication inproportion and restrained untill the harvest, processing and marketing. So itmeans in agribussiness herbs turmeric and galangal should be calculated /analyzed carefully about the advantages and disadvantages, includingdistribution and marketing network.Key word: agribussiness, medicine plant, traditional characteristic, turmuric andgalangal.